Reposisi Muballigh: Dari ‘Personal’ Menuju ‘Agent of Change’ - Asep Shodiqin (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2012)
The tendency of changes in society and rituals of the dakwah implementation in term of verbal missionary propaganda (bi al-lisan) are getting left behind, which in turn has affected the alienation of community members from religious values. In fact, the essence of religion is a value, rather than a ritual aspect. The alienation community members of religious values is a fundamental problem and must be observed and solved. And similarly, structural, socio-economic and socio-cultural problems. Departing from these issues, the necessary propagation models in the community empowerment model, people centered development and value oriented development. This paper described about how ideally a muballigh have to changed their orientation from personal into a more social.